BROADENING THE SCOPE OF RISK FACTORS IN PREDICTING STAGE II COLON CANCER OUTCOMES - Xusanboy Mamatolibovich Raubjonov; Xushid Tursunmurodovich Normurodov (Web of Journals Publishing, 2025)
In this editorial, we examine the article by Wu et al., offering a critical assessment of their viewpoint and evaluating the significance of the findings from Liu et al.'s original clinical research. We believe that several newly identified factors related to colon cancer progression, highlighted in recent clinical studies, should be incorporated into the analysis to improve the accuracy of prognosis. These additional factors — including inflammation, gut microbiota diversity, immune system function, and nutritional status — play important roles in influencing the survival outcomes of patients with stage II colorectal cancer after surgery. Furthermore, we explore the practical application and potential limitations of these expanded analyses in clinical settings. A comprehensive evaluation of each patient’s overall health context is crucial for determining the most effective therapeutic approach.